Linalool, 1,8-Cineole, and Eugenol Transfer from a Curry Dish into Human Urine - Debong, Marcel; N'Diaye, Katharina; Schöberl, Daniela; Yin, Yue; Lang, Roman; Büttner, Andrea; Hofmann, Thomas; Loos, Helene (Molecular Nutrition & Food Research, 2023)
Scope: For most substances, there are several routes of excretion from the human body. This study focuses on urinary excretion of dietary odorants and compares the results with previously obtained results on excretion into milk. Methods and results: Lactating mothers (n = 18) are given a standardized curry dish and donate urine samples before and after the intervention. The odorants 1,8-cineole, linalool, cuminaldehyde, cinnamaldehyde, 4-hydroxy-2,5-dimethyl-3(2H)-furanone, sotolone, eugenol, vanillin, and γ-nonalactone are quantitatively analyzed. A significant transition of up to 6 µg g−1 creatinine into urine is observed for linalool, 1,8-cineole, and eugenol. Maximum concentrations are reached 1.5 h after the intervention for 1,8-cineole and eugenol as well as 2.5 h after the intervention for linalool. Comparison with previous results reveals that the excretion pattern of odorants into urine is divergent from the one into milk. In a second intervention study (n = 6), excretion of phase II metabolites into urine is studied using β-glucuronidase treatment. Linalool and eugenol concentrations are 23 and 77 times higher after treatment than before treatment with β-glucuronidase, respectively. Conclusion: The study demonstrates transition of linalool, 1,8-cineole, and eugenol from the diet into urine and excretion of glucuronides in the case of linalool, eugenol, and vanillin.
CRIS-Team Scopus Importer:2023-12-08
Keywords: aroma transition; gas chromatography-mass spectrometry/olfactometry; maternal diet; milk; phase II-metabolism